SAT0349 Duration of Steroid Treatment in Polymyalgia Rheumatica. (15th July 2016) - Tang, E.; Shah, P.; McKenna, F.
Abstract : Background: The duration of steroid treatment in polymyalgia rheumatic (PMR) is variable. Some patients do not have raised inflammatory markers and anecdotal evidence suggests they may need a shorter duration of treatment. In order to evaluate parameters that may predict the duration of steroid treatment we have undertaken a retrospective analysis of patients on our database with a diagnosis of PMR. Methods: We evaluated patients who presented with new onset PMR to the Trafford Rheumatology Unit between 2005 and 2010. Following a 14 day therapeutic trial of prednisolone 20mg od and a diagnosis of PMR confirmed by a consultant rheumatologist, all patients received a standard reducing regime of prednisolone, reducing every 2 weeks to initial maintenance of alternate day 10mg/5mg after 2 months (if possible). Doses were increased for recurrence of symptoms. After 6 months the dose was reduced to 5mg od if they had not required a dose increase and tailed off once asymptomatic on 5mg od for 6 months. All patients were followed for 10 years or until drug free remission. The electronic records were reviewed for demographic data, blood count, inflammatory markers, liver enzymes, immunology, and duration of treatment prior to drug free remission. Results: 96 patients were evaluated. 15 were excluded from analysis if they had incomplete documentation or because of a positive rheumatoid factor, other immunology or revised diagnosis. The mean age was 68yrs; range 53–90yrs. Female to male ratio was 2.8:1. The median duration of symptoms prior to presentation was 4.5 months (1–36 months). At diagnosis 14% of patients were anaemic, mean CRP was 35mg/l, mean ESR was 45mm/hr and 26% had normal inflammatory markers. Only 1% of patients had raised liver enzymes. 44% were able to reduce to 5mg prednisolone after 6 months and a further 6% after 9 months. The mean duration of steroid treatment for all patients was 30 months (13–108 months). For patients with a normal ESR and CRP at diagnosis, the mean duration of steroids was 22 months compared with 32 months with raised ESR and 35 months with raised CRP. 10% relapsed after steroid withdrawal. 2 patients remained on long term steroids. Conclusions: Approximately 25% of patients with PMR do not have raised inflammatory markers at diagnosis and have shorter total duration of steroids (mean 22 months). Almost half can reduce prednisolone to 5mg after 6 months. The average duration of steroids prior to drug free remission is almost 3 yrs in patients with raised inflammatory markers at diagnosis. 10% relapse after gradual steroid withdrawal. Disclosure of Interest: None declared